Disrupting Oil Markets and Electric Vehicles (EVs) as Game Changers: Examining the EV Purchase Intention of Malaysian Gen Z - Zainal Abidin, Ahmad Zafran Irfan; Mohd Noor, Nurul Hidayana (Journal of Technology Management and Business, 2026)
The ongoing conflicts in West Asia are expected to be a catalyst for a surge in electric vehicle (EV) sales in the country, with the market forecast to double to 8% this year. The problem of environmental pollution has also forced the transportation sector to accelerate the adoption of environmentally friendly EVs. This research aims to examine the relationship between factors influencing EV purchase intention among Malaysian Gen Z in the Southern region. Research data were collected via an online questionnaire distributed through cluster and convenience sampling. Data were processed using Structural Equation Modeling (SEM). Based on a sample of 258 respondents, perceived cost savings, car attributes, subjective norms, and personal environment norms positively influence purchase intention. In contrast, personal environment norms moderate the relationships between car attributes, subjective norms, and EV purchase intentions. Thus, the Malaysian government and relevant agencies need to support the transition to EVs through a series of policies, ranging from subsidies and fiscal incentives to regulations that support the development of charging infrastructure to accelerate EV adoption across all levels of society.